2021
DOI: 10.1538/expanim.21-0060
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of interferon-induced protein with tetratricopeptide repeats 3 relieves the inflammatory response and myocardial fibrosis of mice with myocardial infarction and improves their cardiac function

Abstract: Myocardial infarction (MI) is a common cardiovascular disease with high morbidity and mortality. In this study, we explored the role of interferon-induced protein with tetratricopeptide repeats 3 (IFIT3) in MI. MI was induced by ligation of the left anterior descending coronary artery. Lentivirus-mediated RNA interference of IFIT3 expression was performed by tail vein injection 72 hours before MI modeling.Cardiac injury indexes and inflammatory response were examined 3 days after MI.Cardiac function indexes, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…38 There is also study revealed that knockdown of IFIT3 relieved the inflammatory response and myocardial fibrosis after myocardial infarction. 39 However, the role of IFIT3 in other autoimmune diseases such as psoriasis remains unknown. Therefore, the previously screened IFN-related genes OAS1, USP18, and IFIT3 are significantly overexpressed in psoriasis and have not been previously studied, suggesting that OAS1, USP18, and IFIT3 play important roles in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 There is also study revealed that knockdown of IFIT3 relieved the inflammatory response and myocardial fibrosis after myocardial infarction. 39 However, the role of IFIT3 in other autoimmune diseases such as psoriasis remains unknown. Therefore, the previously screened IFN-related genes OAS1, USP18, and IFIT3 are significantly overexpressed in psoriasis and have not been previously studied, suggesting that OAS1, USP18, and IFIT3 play important roles in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of IFIT3 could significantly suppress the release of inflammatory cytokines in hepatic ischemia‐reperfusion injury via the inhibition of STAT1 and STAT2 phosphorylation 38 . There is also study revealed that knockdown of IFIT3 relieved the inflammatory response and myocardial fibrosis after myocardial infarction 39 . However, the role of IFIT3 in other autoimmune diseases such as psoriasis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…IFITM3 [49] expression is related to the patients with hypercholesterolemia and its progression. Previous studies have shown that IFIT3 [50] might influence the prognosis in myocardial infarction. IFIT1 [51] might be involved in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 might play a role in progression of diabetes mellitus [68]. CXCL10 [69], ISG15 [70], SIGLEC1 [71], CXCL9 [72], IFIT3 [73], KLF15 [74] and SPRR3 [75] have a potential role in the diagnosis and treatment of cardiovascular diseases. CXCL10 [76], SIGLEC1 [77] and IL1R2 [78] have been suggested to be associated with neurological diseases.…”
Section: Discussionmentioning
confidence: 99%